KARAKTERISTIK DAN ASPEK BIOLOGI Scaphopoda (MOLUSKA) - Putri Sapira Ibrahim (OSEANA, 2019)
CHARACTERISTICS AND BIOLOGICAL ASPECTS OF Scaphopoda (MOLLUSCS). Scaphopoda are bilaterally symmetrical marine molluscs, commonly known as the "tusk shells" because their shells are conical. There are approximately 900 species of Scaphopoda, found in soft silty marine sediments, which they burrow in search of food. Scaphopoda feeds on microorganisms, their diet dominated by foraminiferans. Hermaphroditic scaphopoda has been reported but rare. The biodiversity of Scaphopoda had been underestimated because the taxonomic and biological aspects of scaphopoda have not been well studied. Classification, morphology, reproduction, behavior, habitat, and distribution of Scaphopoda are discussed in this paper.